Deteksi Zona Rawan Tsunami Pesisir Kota Bandar Lampung Menggunakan Data Geospasial Berbasis Sistem Informasi Geografis - Iskandar Zulkarnain; I gde Darmaputra; Aniessa Rinny Asnaning (Jurusan Teknologi Pertanian, 2020)
The Bandar Lampung coastal area naturally has the potential of a tsunami hazard. Historically the coastal area of Bandar Lampung City had been hit by a tsunami with a height of 10-30 meters in 1883 when the eruption of Mount Krakatau occurred. The partial collapse of Mount Krakatau, which occurred at the end of 2018, also had a tidal wave impact as high as 1-2 meters in the Bandar Lampung coastal area. This study aims to produce Thematic Maps of Tsunami Hazard Zones in the Coastal Areas of Bandar Lampung City as a source of information for the community and stakeholders. The method used is spatial analysis with GIS through the overlay method. The result shown that eight sub district in Bandar Lampung City are prone to tsunami hazards with risk categories up to very high risk categories.